Community Empowerment in Outermost Small Islands in Maintaining Territorial Integrity and Realizing Indonesian Maritime Defense - Tiwi Gustria Ningsih; Beni Rudiawan; Dohar Sianturi (CV. Rayyan Dwi Bharata, 2023)
Negara Kesatuan Republik Indonesia (NKRI) is an archipelagic country. Indonesia's struggle to gain world recognition as an archipelagic country was first obtained through the Archipelagic State Concept in the Djuanda Declaration on December 13, 1957. Indonesia's maritime territory is an area rich in resources that are beneficial for the welfare of society. So far the development of the outer islands has not shown good results. This is caused by many factors, among others, geographically the location of the outermost islands is difficult to reach, there are limited business scales, methods of exploiting marine resources that are not yet effective, limited facilities and infrastructure, limited ability to manage available natural wealth. This research aims toanalyze community empowerment activities living on these islands as one of the efforts to maintain territorial integrity and realize Indonesia's maritime defense. This research is a qualitative research. The research design is descriptive analysis. The results of this study arecommunity empowerment in the outermost small islands in maintaining territorial integrity and realizing Indonesia's maritime defense through the Service of the Indonesian Navy, Development of Regional Resilience and Social Communication and the Government of Natuna Regency providing various types of assistance, such as socialization of fish farming and fishing gear.The empowerment cooperation carried out by Lantamal IV Batam with the Regional Government of Natuna Regency has not gone well, the actors involved in implementing the empowerment cooperation have not worked together optimally and there are still obstacles faced, namely uniting community empowerment activity programs between Lantamal IV Batam and Natuna Regency.